Research on single carrier signal transmission technology based on channel-detecting in troposcatter communication - QIN Jian-cun 1; 2 (Tongxin xuebao)
The single carrier signal transmission scheme based on channel-detecting in troposcatter communication was introduced according to the characters of the troposcatter channel. Theory analysis and performance evaluation of the troposcatter modem employing this technique were also presented. Finally, comparison between this modem and systems which adopts the best diversity combination was given, which shows highly accordance with theoretical analyzing. Be- sides,complexity of troposcatter communication systems can be greatly reduced by adopting this technique, and it has important reference for development of troposcatter communication.